Perceptions of selected Filipino participants on undue inducement for participation in clinical trials - Montoya, Jaime C.
The main concern of this study was to describe the issue of undue inducement from the perspective of selected Filipino respondents that included clinical investigators and ethics review board (ERB) members. It specifically intended to determine the respondents' perceptions about appropriate and inappropriate monetary and in-kind compensation for clinical trials, the social factors associated with their perceptions, their knowledge and assessment about current compensation packages in the country, their undue inducement concepts and assessment of selected drug trials, as well as their views about Emanuel's four criteria on undue inducement. Descriptive research design utilizing the triangulation of methods particularly survey, focus group discussion, and review of literature were used for the study. The survey had 44 respondents (34 females and 10 males) while the three focus groups had 16 participants. These respondents were purposively drawn from among the participants of the Philippine Council for Health Research and Development's (PCHRD) ethics training workshops which were conducted in three cities from October 2007 to March 2008. A self-administered survey questionnaire and an FGD interview guide served as the research instruments.